Solid oxide cells with zirconia/ceria Bi-Layer electrolytes fabricated by reduced temperature firing1. Issue 18 (14th May 2015) - Gao, Zhan; Zenou, Victor Y.; Kennouche, David; Marks, Laurence; Barnett, Scott A.
<x xml:space="preserve">Abstract</x> Solid oxide cells with thin bi-layer YSZ/GDC electrolytes, with excellent performance and stability, were prepared by a reduced-temperature (1250 °C) co-firing process enabled by the addition of a Fe2O3 sintering aid.